2015
DOI: 10.1016/j.bbadis.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel curcumin analog C66 prevents diabetic nephropathy via JNK pathway with the involvement of p300/CBP-mediated histone acetylation

Abstract: Glomerulosclerosis and interstitial fibrosis represent the key events in development of diabetic nephropathy (DN), with connective tissue growth factor (CTGF), plasminogen activator inhibitor-1 (PAI-1) and fibronectin 1 (FN-1) playing important roles in these pathogenic processes. To investigate whether the plant metabolite curcumin, which exerts epigenetic modulatory properties when applied as a pharmacologic agent, may prevent DN via inhibition of the JNK pathway and epigenetic histone acetylation, diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 52 publications
1
68
0
1
Order By: Relevance
“…4B). Furthermore, density of cells with expression of fibronectin, a major profibrotic cytokine that plays an important role in fibrotic processes [22], was found increased in diabetes group (P b 0.01, compared with control group, Fig. 4C and D) but alleviated upon Danshen injection.…”
Section: Danshen Injection Ameliorated Hyperglycemia-induced Damage Omentioning
confidence: 87%
“…4B). Furthermore, density of cells with expression of fibronectin, a major profibrotic cytokine that plays an important role in fibrotic processes [22], was found increased in diabetes group (P b 0.01, compared with control group, Fig. 4C and D) but alleviated upon Danshen injection.…”
Section: Danshen Injection Ameliorated Hyperglycemia-induced Damage Omentioning
confidence: 87%
“…As described in our previous study (25), EpiQuik™ Tissue ChIP Kit (P-2012; Epigentek Group Inc., Farmingdale, NY, USA) was used to perform the ChIP assay according to the manufacturer's protocol. In brief, the acetylated histone H3 antibody (1 µg, Epigentek Group Inc.) or 1 µl of normal mouse IgG (as a negative control) was used to pre-coat the assay wells.…”
Section: Methodsmentioning
confidence: 99%
“…In a model of diabetic renal fibrosis induced by streptozotocin (STZ), C66, a curcumin analog, blocked glomerular and interstitial fibrosis, which was associated with reduced renal mitogen activated protein kinase (MAPK) signaling [53, 54]. Chromatin immunoprecipitation (ChIP) revealed that C66 reduced STZ-mediated recruitment of p300 to the promoters for the genes encoding CTGF, PAI-1 and fibronectin, and this was associated with reduced H3K9/14 acetylation at these sites.…”
Section: Histone Acetyltransferases (Hats) and Fibrosismentioning
confidence: 99%